The Qur’anic text in the sentences An_Naziat - salh sahood, Khawla (Journal of College of Education, 2022)
The Qur’anic text has a unique peculiarity in the harmony of its structures and sentences, and the Meccan surahs were characterized by strong sounds, rapid rhythm and homogeneous intervals, in which vocal harmony was achieved along with moral harmony. And the fate of criminals. Surat Al-Naza’at is Meccan and its verses are forty-six, characterized by artistic and rhetorical characteristics. I began by swearing by the angels due to the severity of the matter and its horrors, and depicted the Day of Resurrection and the state of the polytheists on the Day of Resurrection.Harmony is evident at all levels of the surah’s verbal, audio, sensory, expressive and rhythmic. The vocal level is one of the most prominent issues that dominate the atmosphere of the surah, and it promotes the expression of its subject, contributes to achieving the ease and beauty of performance and shows new meanings in the Qur’anic text. The research includes a preface on the concept of harmony and four sections, which conclude with the most important results.. The research adopted the descriptive analytical approach that describes the phenomenon of phonetic harmony in Surat Al-Naziat and its rhetorical importance.
Keywords: Phonetic harmony; Surat Al Naza'at; rhetoric